The Role of Physical Literacy in Supporting Physical Fitness Levels: A Holistic Approach to Student Development in Physical Education - Ari Purnomo; Hidayat; Nurlan Kusmaedi; Amung Ma'mun; Nuryadi; Sandey Tantra Paramitha (Universitas Negeri Semarang, 2025)
This study aims to examine the relationship between physical literacy and the physical fitness levels of ninth-grade students in junior high schools across Garut Regency. This study employed a quantitative design with a cross-sectional approach. Physical literacy refers to the integration of motivation, confidence, knowledge, and understanding that enable individuals to engage in lifelong physical activity. Data were collected through the APLQ questionnaire and the Indonesian Physical Fitness Test (TKJI), employing a survey and physical assessment method with 127 participants. The findings revealed a significant correlation between physical literacy and physical fitness, with a significance value of p = 0.013, indicating that physical literacy plays a role in supporting fitness levels. The conclusion that students with higher levels of physical literacy tend to achieve better physical fitness, while lower levels of physical literacy are often associated with poorer fitness outcomes. This study emphasizes the importance of fostering physical literacy as a means to promote active and healthy lifestyles among students.